The Effect of Place, Taste, Menu Variety, and Service Quality on Customer Satisfaction at Marowa Cafe, Batam City - Melda Ramanda; Suyono; Maizar (Penerbit Jurnal Indonesia, 2026)
This study is motivated by the increasing competition in the cafe industry, which requires business owners to continuously improve customer satisfaction as a key determinant of sustainability and repeat patronage. Customer satisfaction in cafe services is shaped by multiple factors related to the overall consumption experience, including physical environment, product quality, menu offerings, and service performance. The purpose of this study is to analyze the effects of place, taste, menu variety, and service quality on customer satisfaction at Marowa Cafe, Batam City, both partially and simultaneously. This research employed a quantitative approach using primary data collected through questionnaires distributed to 100 cafe customers. The data were analyzed using multiple linear regression with the assistance of SPSS version 28.0. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted to ensure the validity of the regression model. Hypothesis testing was performed using t-tests for partial effects, an F-test for simultaneous effects, and the coefficient of determination (R²) to assess the explanatory power of the model. The results of the partial analysis indicate that place, taste, menu variety, and service quality each have a positive and significant effect on customer satisfaction. Among the independent variables, menu variety demonstrates the strongest partial influence, indicating that customers highly value diverse and innovative menu options. The simultaneous test confirms that all independent variables collectively have a significant effect on customer satisfaction. Furthermore, the coefficient of determination reveals that 76.1 percent of the variation in customer satisfaction can be explained by the four independent variables, while the remaining 23.9 percent is influenced by other factors not included in the model. These findings suggest that customer satisfaction at Marowa Cafe Batam is shaped by an integrated experience that combines a comfortable place, appealing taste, diverse menu offerings, and high-quality service. Practically, cafe management should adopt a comprehensive strategy that balances improvements in physical atmosphere, product consistency, menu innovation, and service excellence. This study contributes to the literature by providing empirical evidence on customer satisfaction determinants in a local cafe context and highlights the importance of a holistic approach in managing customer-oriented service businesses.